Elampus spina - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
4. Elampus spina (Lepeletier de Saint Fargeau, 1806) Hedychrum spinus Lepeletier de Saint Fargeau 1806: 121. Holotype ♂; France: Meudon (MSNT) (examined). Elampus productus Dahlbom 1854: 44. Syntypes; Portugal, France (ZMUL). Remarks. This species has been confused with Elampus constrictus in older literature. Sahlberg (1910: 99) and Hellén (1920: 206) reported the species from Finland and Russian Fennoscandia, and Borries (1891: 92) reported it from Denmark (as Notozus productus ). It was at first reported from Sweden by Thomson (1870: 103, as E. productus ), after which it was mentioned by Mocsáry (1889: 68, as Ellampus spina ), Aurivillius (1911: 6) and Jansson (1922: 33, as Notozus spina 1934: 287, as Notozus panzeri var. spina ). All Finnish and Russian Fennoscandian specimens have been checked and found to belong to E. constrictus . It is most likely that also all the Danish and Swedish published records refer to E. constrictus . Rosa & Soon (2012) reported E. spina from Sweden based on an old Swedish specimen deposited in NRM. The specimen was later found to represent a large individual of E. foveatus . Apparently E. spina is a predominantly South European and West Asian species, with some scattered records from central Europe (Banaszak 1980). : Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on page 51, DOI: 10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433 : {"references": ["Lepeletier de Saint Fargeau, A. L. M. (1806) Memoire sur quelques especes nouvelles d'insectes de la section des Hymenopteres, appeles les Porte-tuyaux, et sur les caracteres de cette famille et des genres qui la composent. Annales du Museum d'Histoire Naturelle, Paris, 7, 115 - 129.", "Dahlbom, A. G. (1854) Hymenoptera Europaea praecipue borealia, formis typicis nonnullis specierum generumve Exoticorum aut Extraneorum propter nexum systematicum associatis, per familias, genera, species et varietates disposita atque descripta. 2. Chrysis in sensu Linnaeano. Friedrich Nicolai, Berlin, xxiv + 412 pp. + 12 pls. http: // dx. doi. org / 10.5962 / bhl. title. 15890", "Sahlberg, J. (1910) Lyhyt katsaus Suomen kulta-ampiaisiin (Chrysidae). Luonnon Ystava, 14, 94 - 99.", "Hellen, W. (1920 [\" 1919 \"]) Uber finlandische Goldwespen. Meddelanden af Societas pro Fauna et Flora Fennica, 46, 203 - 213.", "Borries, H. (1891) Oversigt over de danske Guldhvepse. (Chrysididae danicae). Entomologiske Meddelelser, 3, 84 - 96.", "Thomson, C. G. (1870) Ofversigt af de i Sverige funna arter af Slagtet Chrysis Lin. Opuscula Entomologica, 2, 101 - 108.", "Mocsary, A. (1889) Monographia Chrysididarum orbis terrarium universi. Musaei Nat. Hungarici Adiuncto, Academiae Scientiarum Hungaricae Socio. Typis Societatis Franklinianae, Budapest, 643 pp.", "Aurivillius, C. (1911) Svensk insektfauna XIII. Hymenoptera. 2. Guldsteklar. Tubulifera. Entomologisk Tidskrift, 32, 1 - 12.", "Jansson, A. (1922) Faunistiska och biologiska studier over insektlivet vid Hornsjon pa norra Oland. Arkiv for Zoologi, 14, 1 - 81.", "Rosa, P. & Soon, V. (2012) Fauna Europaea: Chrysididae. In: Mitroiu, M. - D. (Ed.), Fauna Europaea: Hymenoptera, version 2. 5. Available from http: // www. faunaeur. org (accessed 1 November 2013)", "Banaszak, J. (1980) Zlotolitki Chrysididae. Katalog Fauny Polski, 26, 1 - 52."]}